M Meta-analisis Pengaruh Model Pembelajaran TGT terhadap Minat Belajar Siswa Sekolah Dasar - ni nyoman kurnia wati (UNHI PRESS, 2020)
This study aims to determine how much influence the (effect size) Teams Game Tournament (TGT) Learning Model has on the learning interest of elementary school students. This type of research is a meta-analysis research using data collection techniques in the form of literature analysis on previous research. The data obtained were analyzed using quantitative descriptive data analysis. This analysis is used to analyze the effect size calculation data obtained from comparing the mean and standard deviation of previous studies. Based on the results of the analysis, it can be concluded that the Teams Game Tournament (TGT) learning model in elementary school learning can be carried out on variables and on subjects and is supported by appropriate learning media. Testing the magnitude of the influence of the Teams Game Tournament (TGT) learning model in learning in elementary schools has a high category, is very feasible and supports to be carried out in learning, especially in elementary schools.